The impact of the Corona pandemic on the banking customer In the commercial loan contract - عبد, اندلس حامد (Journal of Legal Sciences, 2021)
The Corona pandemic affected all different areas of life, as the world is facing a challenge at the present time as a result of the Corona pandemic and the economic turmoil it left behind, and many countries have tended to address the economic effects of the Corona pandemic by resorting to borrowing internally or externally to cover their needs.The activity of banks is affected by many things, including, and the research aims to solve the problems related to the commercial loan contract in light of the crises, and that the initiatives that many countries have followed call to reduce the harm inflicted on citizens, such as economic burdens, by postponing installments in light of the crisis and postponing all credit dues to banks on customers. Of institutions and individuals, and not to impose additional fines for late payment in light of the Corona pandemic to face this exceptional circumstance according to specific and sound procedures, and banks should achieve a balance between granting the loan and the size of risks in banks